TINJAUAN HUKUM ISLAM TERHADAP IJARAH POHON MANGGA - Shobani Shobani (UIN Siber Syekh Nurjati Cirebon, 2016)
Abstract The perfect relationship is the relationship of exchanges where someone gave what he had for the people then he got something useful to him as needed. This relationship in the Islamic fiqh is called al-Ijarah. Al-Ijarah is a type of contract that benefited from a rented object with the path of the turn. As for the lease of the Qur'an has been organized and elucidated with hadis.Indramayu is mango city with mango tree that was developed in the city. Local people rent manggo trees. Trees for rent then taken by the tenant as a result and benefit of goods for rent.From the research concluded, in terms of subject matter, both people that have agreed in the lease of the mango tree is valid because it has been Â fuliflled the terms people in agreement and the existence of an agreement between the two sides. But in terms of objects, goods or rent object is invalid, because it is the practice of selling fasid and otherwise